Application of machine learning for stock index forecast - Khoo, Edwin Ding Neng (Nanyang Technological University, 2020)
Stock Prediction has always been a popular area of research. However, in the last decade, the advances in machine learning has brought about new possibilities with new algorithms and models that can be utilized in stock prediction. With the newfound interest, it sparked a growing amount of research into the subject.